Profitability analysis by agricultural subsector in Colombia and its business features for the 2009-2013 term - Arias Robles, Milena Esther; Mercado Fernández, Teobaldis; Feria Díaz, Jhon J. (PalArch's Journals, 2024)
A balanced and refined data panel of 4,412 companies part of the Sistema de Información y Reporte Empresarial, SIREM, [Business Information and Report System] was built to analyze profitability behavior by agricultural subsector in Colombia and its business featuresfor the term of 2009-2013.Return indicators on assets - ROA, operating margin and turnover were calculated with this. Positive and negative fluctuations in agricultural profitability were estimated with great opportunities for improvement for the business management. It is noted that the export-type subsectors make inefficient use of their assets, restraining sustained increase of business profitability.